Gender and age characteristics and atrial fibrillation during long-term telemonitoring of the ECG - V.M. Bogomaz; I.O. Berdnyk; L.I. Lysa (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the possibilities of long-term patch monitoring of the electrocardiogram (ECG) to determine gender and age characteristics of the frequency of detection of atrial fibrillation (AF). Materials and methods. A total of 1,123 patients participated in this 2-year (2021–2023) retrospective multicenter study. Long-term ECG monitoring was performed at the referral of internists and cardiologists of 30 health care institutions according to various clinical indications for this study. For long-term monitoring of the ECG, the innovative device «Mawi Heart Patch» was used – a disposable two-channel device with the possibility of continuous recording of the ECG for up to 7 days. The primary analysis of the records was carried out using Cardio.ai artificial intelligence algorithms, re-decryption and validation by certified doctors. Results. The average age of the study participants was (50.2 ± 16.65) years. There were 599 (53.3 %) women, 524 (46.6 %) men. The average time of ECG monitoring was (81.03 ± 18.5) hours, 74.35 % of the participants had continuous ECG monitoring for 3 days, 20.75 % for 4 days, and 2.58 % for 5 days. In total, AF was diagnosed in 7.93 % of patients, in particular, women and men were 6.51 % and 9.54 % respectively (p > 0.05). In elderly patients, AF was diagnosed statistically significantly more often than in middle-aged patients (18.5 and 3.6 %, respectively, p ˂ 0.001). Among all age groups, the highest frequency of detection of AF was in participants over 75 years old, compared to young (28.8 % vs 3.6 %, p ˂ 0.001) and middle-aged patients (28.8 vs 18.5 %, p ˂ 0.05). Conclusions. The study did not reveal a gender difference in the frequency of diagnosing AF. In patients over 50 years, a significant increase in the frequency of detection of AF was recorded, which tends to increase in the following age periods and reaches a maximum in long-livers (over 90 years). The use of long-term patch ECG monitoring in patients of older age groups expands diagnostic possibilities and makes it possible to prevent complications in time.